2013
DOI: 10.1017/jfm.2013.459
|View full text |Cite
|
Sign up to set email alerts
|

Active suspensions in thin films: nutrient uptake and swimmer motion

Abstract: A numerical study of swimming particle motion and nutrient transport is conducted for a semidilute to dense suspension in a thin film. The steady squirmer model is used to represent the motion of living cells in suspension with the nutrient uptake by swimming particles modelled using a first-order kinetic equation representing the absorption process that occurs locally at the particle surface. An analysis of the dynamics of the neutral squirmers inside the film shows that the vertical motion is reduced signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 48 publications
2
62
0
Order By: Relevance
“…The time correlation function of these density fluctuations shows oscillatory behavior with a well defined frequency. Recently, the dynamics of many squirmers confined between two hard walls has also been studied [161,254,[342][343][344]. For a separation distance much larger than the swimmer size, a huge dynamically evolving cluster again emerges.…”
Section: Microswimmers With Hydrodynamic Interactionsmentioning
confidence: 99%
“…The time correlation function of these density fluctuations shows oscillatory behavior with a well defined frequency. Recently, the dynamics of many squirmers confined between two hard walls has also been studied [161,254,[342][343][344]. For a separation distance much larger than the swimmer size, a huge dynamically evolving cluster again emerges.…”
Section: Microswimmers With Hydrodynamic Interactionsmentioning
confidence: 99%
“…This finding was predicted by Magar et al (2003) imposing a boundary condition for nutrient uptake that takes into account both the absorption of nutrients and the nutrient diffusion inside of the cell. Lambert et al (2013) also found that, as the volume fraction of squirmers increased, the squirmers consumed less nutrients and required more power for the same swimming motion. These findings are important in understanding nutrient uptake in a confined environment.…”
Section: Introductionmentioning
confidence: 84%
“…In the non-dilute regime, nutrient uptake by a swimming micro-organism has received little attention, except for Lambert et al (2013). However, mixing of chemicals and tracers in non-dilute suspensions of cells has been reported by many researchers (Pedley & Kessler 1992;Hill & Pedley 2005;Ishikawa 2009;Ishikawa, Locsei & Pedley 2010;Koch & Subramanian 2011;Kurtuldu et al 2011;Molina & Yamamoto 2014;Wagner, Young & Lauga 2014;Goldstein 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations